PENATAAN PURA DESA WONOREJO KECAMATAN SILIR AGUNG KABUPATEN BANYUWANGI JAWA TIMUR - Susanta, I.N.; Lanus, I.N.; Swanendri, N.M.; Manik, I.W.Y. (Buletin Udayana Mengabdi, 2017)
Pura Desa Wonorejo located in the village Wonorejo, District Silir Agung, Banyuwangi. Pura cuddly by the people of this village, its existence is not only related to people Wonorejo village, but also the people in the surrounding rural areas who do not have a temple. Currently, the general physical condition of the temple can be good, but in some ways still requires juggling upstream-teben related concepts that transformed the building palinggih Widhi-gods and ancestors. Not efektif palinggih area at the rear, while on the other hand felt natah there is not adequate in certain ceremonies. The realization that these conditions interfere with the smooth conduct of religious activity, comfort and confidence. These conditions have encouraged pengempon, administrators and stakeholders to conduct planning activities. Structuring activity itself begins with planning which is supported by the academic community through the Department of Architecture, University of Udayana service activities 'Grant Udayana Serve'. The activities of planning and design in this devotion consists of several stages starting from the beginning / introduction, preparation, proposal submission, evaluation and action. Of the process that was followed was agreed and stipulated that all the buildings take shape and pattern of Javanese architecture, so it can conservation accordance with the culture and the local environment.